Facets of coordination chemistry - Agarwala, B. V. (Badri Vishal); Munshi, K. N. (Kailash Nath); Dey, Arun K., 1922-; World Scientific (Firm) (Singapore ; River Edge, N.J. : World Scientific Pub. Co., 1993)
A concise account of coordination chemistry since its inception is given here together with some of the newer significant facets. This book covers a broad spectrum of various topics on Environment, Cyclic Voltammetry, Chromatography, Metal Complexes of biological interest, Alkoxides, NMR spectroscopy and others. These are useful to the scientific community engaged in the field of Inorganic Chemistry and Analytical Chemistry.
1. Introduction: coordination chemistry and its multifacets / B.V. Agarwala and K.N. Munshi -- 2. Coordination chemistry of environment / D.F. Marim -- 3. Retrospective studies on metal complexes as synthetic dioxygen carriers of biological interest / F. Basolo -- 4. Heterometal alkoxides: a novel series of stable polymetallic coordination compounds / R.C. Mehrotra -- 5. Solvent effects on the reactions of coordination complexes / A.C. Dash, R.K. Nanda and S. Aditya -- 6. A simple model for fitting properties of binary mixtures / E. Högfeldt -- 7. Donor-acceptor interactions and structural flexibility of coordination-compounds in solution / W. Linert -- 8. NMR spectroscopy of oriented systems: application to weak molecular complexes / C.L. Khetrapal -- 9. Cyclic voltammetry / R.C. Kapoor -- 10. Chelating polymers / C.-Y. Liu and K.L. Cheng -- 11. Optical resolution of metal complexes by column-chromatography / M. Fujita and Y. Yoshikawa -- 12. Correlation between the composition and structure of transition metal complexes and their R[symbol] values obtained by planar chromatography / G. Vuckovic, Z.L. Tesic and M.B. Celap -- 13. Some designs of polyethers for use in membranes of ion-selective electrodes / J.D.R. Thomas -- 14. Copper proteins and their various roles in biological systems / P.K. Bhattacharya -- 15. Urinary stones, diet and folk medicine / A.K. Banerjee, M.H.A. Akhbari Shad and S.K. Roy.
Articles by the students and colleagues of Arun K. Dey in honor of his 70th birthday.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Coordination compounds; Electronic books